Politeness strategies used by children in requests in relation to age and gender: a case study of Jordanian elementary school students - Al-Abbas, Linda S. (Frontiers in Education, 2023)
Introduction Requesting is considered one of the most threatening speech acts that people tend to use politeness strategies to tone down the request and minimize the face loss of the recipient. These strategies develop over years and while children appear to produce polite speech forms at an early age, less is known about the strategies they use when they make requests in the Jordanian context. This study aims to investigate politeness strategies used by Jordanian children in requests at different age levels in relation to their gender. Methods The study included 80 subjects divided into two age groups, namely, six years and ten years, with an equal number of boys and girls. They met a lady puppet who had a box of gifts, and they were told to ask her politely to get the gift they wanted. Their requests were recorded and analyzed using Blum-Kulka’s politeness model to find the most common strategies the children used and whether these strategies differed with age and gender. Results and Discussion The study concluded that at the age of six, the concept of politeness is present in children’s linguistic competence, but the assignment of polite expressions to the proper speech act is still ill-defined. There were no significant differences in using politeness strategies according to gender. As children grow older, around the age of ten, they become more able to express politeness in requests. Girls preferred the indirect strategies while boys opted for the direct level in making requests. This study may positively help parents and schoolteachers enhance the pragmatic knowledge and linguistic politeness of children.